Childfree in a Variety of Perspectives: Philosophical Perspectives, Islamic Family Law and Contemporary Social Life - Rahmad Efendi; Zulpahmi Lubis; Mhd Nurhusein Daulay; Tri Eka Putra Muhtarivansyah Waruwu; Nurman Ritonga (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The childfree phenomenon has become a hot topic in contemporary society. This choice not only reflects the dynamics of modern lifestyles but also raises legal, social, and religious controversies. This research aims to analyze childfree law from various perspectives, namely legal philosophy, Islamic family law, sociology, and anthropology, as well as career and population aspects. A multidisciplinary approach is used to understand this phenomenon in its entirety and comprehensively. From the perspective of Islamic law, child freedom is considered contrary to maqashid al-shariah, especially in safeguarding offspring (hifzh al-nasl), which is one of the purposes of marriage. However, from the perspective of legal philosophy, such decisions can be justified through the principles of personal autonomy and freedom of choice. Meanwhile, sociological and anthropological perspectives view childfree as a reflection of changes in social structure, individualistic values, and the influence of modern economics and lifestyle. In addition, career factors and population density also influence these preferences, which indirectly impact demographics and development. This study shows the importance of a balanced approach between religious norms, individual freedom, and social responsibility in responding to the childfree phenomenon in the modern era.